Jus Tomat Meningkatkan Kepadatan Tulang Tikus Menopause (TOMATO JUICE INCREASE BONE DENSITY OF MENOPAUSE RATS) - Laswati, Hening; Hendarto, Hendy; Irawati, Dian; Mahaputra, Laba (Jurnal Veteriner, 2015)
Osteoporosis in postmenopausal women happened due to estrogen deficiency which leads imbalancebone-formation and bone-resorption process. Recently, phytoestrogen as an alternative hormon replacementtherapy in postmenopausal women could overcome estrogen deficiency. The objectives of this study was toevaluate the effect of tomato juice administration and combination of physical exercise on bone density inestrogen deficiency condition. Twenty eight postovarectomy female rats (Rattus novergicus) were randomizedinto four experiment groups : the controlled group ( 2 mL aquades administration); the exercised group(swimming for 30 minutes, three times in one week), the tomato juice administration every day (44 mg/200g body weight), and the combination exercise and tomato juice administration. Four weeks after treatmentthe samples were collected from os femure for morphological examination. The intervention groups showeda significant difference in bone density with the control group (p<0.05). Bone density highest on the tomatojuice administration group. There is significant difference bone density between tomato juice administrationgroup and the combination group (p<0.05), but no significant difference between physical exercise groupand the combination group. Tomato juice showed an increasing bone density on estrogen deficiencycondition and the combination group have the same effect with the exercised group.
Keywords: osteoporosis, tomato juice, physical exercise, bone density